Power grid ice coating medium-short-term prediction method based on blocking high index - ZHANG JIE; FENG TAO; LU JIAZHENG; LI LI; XU XUNJIAN; DI YUELUN (2017)
The invention discloses a power grid ice coating medium-short-term prediction method based on a blocking high index. According to the method, the relation between factors such as the blocking high intensity, the blocking high position, the blocking high area, and the blocking high duration etc. and domestic power transmission line ice coating is comprehensively considered, parameterization of the factors is performed through quantified indexes, the relation between the existed blocking high and the domestic power transmission line ice coating is fully utilized, a power transmission line ice coating medium-term prediction method is provided, the intelligence and the automation of ice coating prediction and early warning of power transmission lines are improved, and the effect and the benefit of prediction and early warning are fully achieved. 本发明公开了种基于阻塞高压指数的电网覆冰中短期预测方法，其综合考虑阻塞高压的强度、阻塞高压的位置、阻塞高压的面积、阻塞高压持续时间等因素与我国境内输电线路覆冰的相关关系，通过定量化的指数对各因子进行参数化，充分利用已有的阻塞高压与我国境内输电线路覆冰发生的关系，提供种输电线路覆冰中期预测方法，提高输电线路覆冰预测与预警的智能化和自动化，充